Clinical evaluation of the efficacy of fractional radiofrequency for the treatment and reduction of stretch marks: A prospective study. (24th October 2022) - Adatto, Maurice
Abstract: Background/Objectives: Skin resurfacing with fractional radiofrequency results in reepithelization, collagen shrinkage, fibroblast stimulation, and neocollagenesis which may be beneficial for the improvement of various skin lesions. This clinical study was conducted to evaluate the safety and efficacy of fractional radiofrequency device (FRF) for the treatment of striae. Methods: Seventeen subjects, totaling 67 treatment zones were evaluated. Subjects had 4 FRF treatment sessions to the striae areas, at 4‐weeks interval. 3D‐standardized photographs of the treatment area with a 3D camera were used to evaluate striae volumetric improvement from baseline to follow up (FU) visits at 12 and 16 weeks post‐final treatment. A satisfaction questionnaire was completed by subjects at each of the follow‐up visits. Additionally, the mean scores of the live investigator assessments of Global Aesthetic Improvement Scale (GAIS), Subject Satisfaction Scale, Pain Visual Analog Scale and Tolerability Score were calculated. Results: A total of 15 subjects completed the study (Fitzpatrick skin type I‐III, average age 36.2 years) received 4 FRF treatments on multiple different body zones with multiple passes over stretch marks on the abdomen, inner arms, lower buttocks, inner thighs, and/or flanks. Analysis of 3D photographs of the striae affected zones at 16‐week FU revealed an average reduction in the striae volume of 19.1%, a reduction of redness of 14.3%, a reduction of pigmentation of 11.2%, and a reduction of striae color of 8.82%. The GAIS improved by 1.7‐points when compared to baseline. Treatments were well tolerated with subjects reporting a mean score of 3.8 out of 10 for pain and 3.1 out of 4 for tolerability (indicating the treatment was "tolerable"), with no occurrences of serious adverse events. The average subject satisfaction at 16‐week follow‐up was 3.1, out of a total of 4, which signified subjects were "satisfied" with their treatment. Conclusion: 3D Image analysis of the treated zones presented overall reductions in the color and texture of striae after four treatments with FRF. A combination of ablation and coagulation introduced by FRF treatment resulted in improvement to the appearance of the treated striae.